Lifespan Socioeconomic Context: Associations With Cognitive Functioning in Later Life - Scott, April B (J Gerontol B Psychol Sci Soc Sci, 2019)
OBJECTIVES: Early socioeconomic status (SES) correlates with later-life cognition. However, the effect of socioeconomic context (SEC), which reflects influences from broader ecological contexts, has not been examined. The present study developed a measure of SEC using lifetime residential addresses and examined SEC and residential mobility effects on later-life cognition. METHOD: Older adults (N = 117, M(age) = 75) reported addresses since birth. Latent SEC was constructed from census income, employment, and education (1920–2010) for each county and census year, extrapolated between census years. Controlling for current SES, SEC in childhood (ages 0–18) and adulthood (ages 19–60), with finer granulations in young adulthood (ages 19–39) and midlife (ages 40–60), predicted later-life cognition. Effects of residential mobility on later-life cognition were also examined. RESULTS: Higher childhood and adulthood SEC were associated with better Auditory Verbal Learning Test recognition (β = .24, p = .012) and immediate recall (β = .26, p = .008). Higher midlife SEC was associated with faster task switching (β = .26, p = .025) and better task switching efficiency (β = .27, p = .022). Higher residential mobility in childhood was associated with higher crystallized intelligence (β = .194, p = .040). DISCUSSION: Independent of current SES, childhood and adulthood SEC predicted later-life cognition, which may be sensitive to effects of social institutions and environmental health. SEC assessed across the lifespan, and related residential mobility information may be important complements to SES in predicting later-life cognitive health.